Active visual control of robot arm - Yau, Wei Yun. (2009)
The use of vision system to control a robot arm increases the flexibility of the robot arm in executing its tasks. At present, such eye-hand coordination is mostly implemented using rigid or passive camera system. Usually, camera calibration is required to recover the homogeneous transformation matrix and to reconstruct the three dimensional world in the robot space based on the image data acquired. However, the passive camera system limits the operating range and the accuracy of the eye-hand system. Increasing the operating range of such a system inevitably reduces the achievable precision and vice versa. Furthermore, the need for camera calibration causes the system to be sensitive to perturbations of the vision system. The work presented is an attempt to address these shortcomings.